Problematic Dilemma of The Limitation of Granting Remission for Corruption Prisoners - Maroni Maroni; Nenny Dwi Ariani (Fiat Justisia: Jurnal Ilmu Hukum, 2018)
Corruption is an extraordinary crime, so the law enforcement for corruption cases must also be done extraordinarily. Therefore, the corruption prisoners or corruptors should be differentiated by their pattern of guidance in Penitentiary. The difference in the process of fostering in Penitentiary is in the form of limitation of granting remission for corruptors. The existence of such restrictive policy poses a problem dilemma to the guidance of current corruption prisoners based on Penitentiary System. This is because the penitentiary system essentially sees the crime of "deprivation of liberty" against a person is only "temporary" so that there is a reduction in criminal or remission for every prisoner. The problem is how to overcome the dilemma of granting remission for corruptors in the perspective of the correctional system. The research method is normative juridical with the regulation of law and doctrinal approach. The result of this research is to overcome the dilemma of granting remission for corruptors by revising Government Regulation Number 99 of 2012 on Terms and Procedures Implementation of Rights of Citizens Correctional Penitentiary that distinguishes the requirements for corruption prisoners that cause losses of state in the high or low nominal. For the corruption prisoners that doing corruption in the high nominal to get the special requirement for granting remission should be added in the high profile corruption prisoners are required to accomplish morality education on the nation and homeland patriotism at their expenses. While the lower profile ones are required to following the common standard coaching for general prisoners. Keywords: Remissions, Corruption Prisoners, Corruption, Correctional System